Respiratory complications after adenotonsillectomy in high‐risk children with obstructive sleep apnea: A retrospective cohort study. Issue 3 (23rd October 2019) - Ekstein, Margaret; Zac, Lilach; Schvartz, Reut; Goren, Or; Weiniger, Carolyn F.; DeRowe, Ari; Fishman, Gad
Abstract : Background: Obstructive sleep apnea (OSA) occurs in 1%‐4% of children; adenotonsillectomy is an effective treatment. Mortality/severe brain injury occurs among 0.6/10 000 adenotonsillectomies; in children, 60% are secondary to airway/respiratory events. Earlier studies identified that children aged <2 years, extremes of weight, with co‐morbidities of craniofacial, neuromuscular, cardiac/respiratory disease, or severe OSA are at high risk for adverse post‐operative respiratory events (AE). We aimed to: Firstly, investigate which risk factors were associated with AEs either in the post‐anesthesia care unit (PACU), pediatric intensive care unit (PICU), or both in this population. Secondly, we investigated factors associated with post‐operative PICU AE despite no event in the PACU in order to predict need of post‐operative PICU after their PACU stay. Methods: Retrospective study of children admitted to the PICU after adenotonsillectomy between 08/2006‐09/2015. Demographics, risk factors, and occurrence of AE (oxygen saturation <92, stridor, bronchospasm, pneumonia, pulmonary edema, re‐intubation) were recorded. Results: During the studied time period 4029 tonsil/adenoid procedures were performed in 3997 children. 179, admitted to the PICU post‐operatively, met criteria for analysis. PICU AEs occurred in 59%: 44%‐83% in any particular risk category. PACU AEs occurred in 42%. Of those with PACU events: 92% suffered AEs in the PICU; however, 35% of those without a PACU AE still suffered a PICU AE. Conclusions: Among high‐risk children undergoing TA, absence of adverse events in PACU during a 2‐hour observation period does not predict absence of subsequent AEs in the PICU .